Pergeseran Bahasa Ibu Dari Bahasa Daerah Ke Bahasa Nasional: Evidensi Pada Anak Usia Prasekolah - Eka wijiyati lestari; Icuk Prayogi; Murywantobroto (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
The shift of mother tongue among preschool children in Central Java is becoming increasingly evident, marked by a decline in the use of regional languages, which can threaten the preservation of local languages and weaken children's cultural identity. This study aims to understand the condition of mother tongue shift in preschool children, the factors causing it, and the efforts that can be made to preserve the mother tongue. This research uses a sociolinguistic approach with a qualitative descriptive method. Data were collected through observation, interviews, and listening techniques, both participatory and non-participatory listening, with preschool children in Margomulyo Village, Juwana District, Pati Regency, Central Java. The results of the study show that Indonesian is more dominantly used by children in daily life, while the use of regional languages is beginning to decline. This shift factor is caused by the family environment, school environment, media and technology, as well as society's perception of regional languages. Efforts that can be made include cooperation between the family, teachers, and the government in habituating and instilling a sense of pride in using regional languages among children. Keyword: language shift, mother tongue, regional language, preschool-aged children, Central Java.